(untitled) (Journal of Engineering, 2013)
Self-compacted concrete (SCC) considered as a revolution progress in concrete technology due to its ability for flowing through forms, fusion with reinforcement, compact itself by its weight without using vibrators and economic advantages. This research aims to assess the fresh properties of SCC and study their effect on its compressive strength using different grading zones and different fineness modulus (F.M) of fine aggregate. The fineness modulus used in this study was (2.73, 2.82,2.9& 3.12) for different zones of grading (zone I, zone II& marginal zone(between zone I&II)) according to Iraqi standards (I.Q.S No.45/1984).Twelve mixes were prepared, each mix were tested in fresh state with slump, V-Funnel and L-Box tests, then 72 concrete cubes of (100*100*100) mm for different mixes were tested for compressive strength after 7 and 28 days of water curing. Results indicated that the combined effect of fineness modulus and grading zone were clear on the passing ability and little effect of grading zone on flow ability and viscosity of fresh SCC properties. Compressive strength decreases with increasing F.M and no effect of grading zone for F.M higher than 2.90